Análise da influência da β-ciclodextrina no tingimento de poliamida com corante ácido - Augusto, Sarah Pignagrandi Camargo (2015)
Dyeing is considered within the textile sector, one of the largest waste generators due to the large consumption of water and chemicals, factors that maximize their pollution potential. In addition to synthetic dyes that have complex molecular structure and difficult to biodegradation, other chemicals are used in the dyeing process with the aim of further improvements in the adsorption of the dye, increasing the fixing performance, better distribution in the material, contributing to a good equalization and quality in the article. Within this context, cyclodextrins (CDs) has aroused great interest in the scientific community, as well as being biodegradable and non-toxic are able to form complexes that modify characteristics of substances. Recently, studies that aim to apply the CDs in textile dyes in order to replace the synthetic auxiliary products are being developed, as the market is increasingly looking for ecotêxteis products and excellence in quality. The ability to incorporate dyes in their cavities causes the CDs can act as retarding agents in the dyeing process, providing improved color uniformity. Thus, this study aimed to study the influence of β- cyclodextrin in polyamide dyeing kinetics with acid dye. The study showed that the size of the dye molecule and compatible cyclodextrin in the complexation affects directly and therefore in delaying or not the dyeing process. Furthermore, it was observed that the temperature is one factor that modifies the behavior of cyclodextrin and the amount of adsorbed values. The dimensions not compatible between the dye molecules and cyclodextrin complexation indicated that the dye occurred more than one cyclodextrin molecule. In dyeings carried out it was observed that the CD does not act as a flame retardant due to decreased equilibration time. In the dyeing 50°C there were no significant changes in the amount adsorbed, unlike the dyeing at 90°C, which was considerable change, indicating that CD has acted as a solubilizer and may promote better equalization. Furthermore, due to the increased solubility and the amount adsorbed, a lower dye concentration can be used to achieve the desired shade. In dyeing performed at 50 ° C with and without CD insertion, the model that best fit was the pseudo-second order as well as in the dyeing to 90 ° C with use of CD. Already at 90 ° C without dyeing the CD was the best fit pseudo-first order, indicating that with the increase in temperature and use of cyclodextrin is no change in kinetic model.